Promoting Pro-environmental Beliefs and Behaviour: Choose-Your-Own Story Futuristic Climate Game - Lala Muradova; Edana Beauvais (PLoS ONE, 2025)
How can we address climate scepticism and increase public support for ambitious pro-environmental policies? This study investigates the potential of future-oriented perspective taking, using an innovative and futuristic choose-your-own-adventure narrative game. This cutting-edge intervention involves living in the life of a future self and making choices related to hypothetical climate crises. The choose-your-own-adventure game was integrated into online survey experiments in the United Kingdom (N = 1,738) and the United States (N =  1,290). We found that participation in the game elicited strong emotional responses in individuals, making them more empathetic, but also more hopeless and sad. Imagining their future self during the climate game enhanced people’s willingness to engage in future discussions about climate change among the UK respondents. Yet, the intervention did little to transform people’s pro-environmental beliefs, policy support, or willingness to sign a climate petition. Causal mediation analyses reveal that these null effects hide important direct and indirect effects. Empathic concern mediates significant positive indirect effect of climate game on people’s pro-environmental beliefs, but negative indirect effect on willingness to sign the climate petition. Empathy seems to shape environmental beliefs and behaviours in diverse ways, highlighting the complex and nuanced relationship between them. These findings offer important implications for recent research on the role of emotions in climate change communication, environmental psychology, and policymaking. We also present a unique approach to fostering empathy for the environment and future generations through an engaging choose-your-own-adventure game.